ECONOMIC FEASIBILITY STUDY FOR PAPER WASTE RECYCLING PROJECT - Barbaz D. S., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The aim of this study is to investigate the economic feasibility of paper recycling factories in Iraq by studying the technical, marketing and financial feasibility to establish a paper-recycling factory in Najaf Governorate and to show the importance of these projects in achieving sustainable efficiency as well as achieving economic efficiency. The expected investment and operating costs were estimated and then the economic profitability criteria were adopted in addition to conducting a sensitivity analysis and determining the break-even amount. The research hypothesis was proven, which confirms that there is an economic, an environmental and marketing feasibility for paper waste recycling projects, as it was found that the project recovers all the money invested in it within a year and a month and a half, and the accounting return rate reached 82%. The net present value was (78,403,069,418) Iraqi dinars, while the discounted profitability index criterion was about (2.546). The internal rate of return criterion was (115%). The risk analysis proved that the project can withstand a 60% decrease in its revenues, and the break-even point quantity was about 1729 tons. The sensitivity analysis also proved that the project is insensitive to changes in investment costs and operating costs, and insensitive to fluctuations in the prices of the project's products. In light of the results, it was found that the project is economically feasible. The study recommended the need to support waste recycling projects as they contribute to achieving environmental sustainability and economic efficiency.